New Lookup Tables and Searching Algorithms for Fast H.264/AVC CAVLC Decoding - LEE, Jun-Young; LEE, Jae-Jin; PARK, SeongMo (IEEE transactions on circuits and systems for video technology, 2010)
In this paper, new codeword structures, tables, and searching methods for fast and efficient coeff_token , total_zeros , and run_before decoding are developed. This new achievement is mainly based on the fact that the context-adaptive variable length coding (CAVLC) decoding can be modeled as a finite state machine. In order to quantitatively evaluate the proposed method in terms of decoding speed and complexity, we define the iteration bound (1/τ̃) and the complexity ratio ( CR ). Using these gauge variables, we show that the new algorithms reduce τ̃ to about one third and complexity ratio to 0.95. This means that the proposed techniques reduce the decoding time to about one third and memory access count by 90% compared to those of the conventional methods without implementation overheads. Multiple-symbol parallel decoding method for run_before syntax element is proposed based on a bit-positioning with the critical path latency of only one multiplexer for the post-combination process. The proposed methods make it possible to implement a fast and efficient CAVLC decoding without losing video quality on any environments.